2020
DOI: 10.1108/lht-08-2019-0166
|View full text |Cite
|
Sign up to set email alerts
|

An environmental scan of virtual and augmented reality services in academic libraries

Abstract: Purpose The growing popularity of virtual and augmented reality (VR and AR) technologies, and increased research into their educational uses, has seen them appearing in a significant number of academic libraries. Little is known, however, about how many libraries have actually adopted these technologies or how they have structured library services around them. The purpose of this paper is to answer these questions. Design/methodology/approach The authors surveyed the websites of the Association of Research L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
(16 reference statements)
0
18
0
2
Order By: Relevance
“…Technology has now been widely used for improving cultural services and is not just limited to academia or libraries (Dalili Saleh et al , 2021; Greene and Groenendyk, 2021; Noh, 2021; Suen et al , 2020; Zhou et al , 2021; Li and Liu, 2022; Xin, 2022). In particular, virtual reality (VR) and augmented reality (AR) has drawn much attention.…”
Section: Using Contemporary Technologies In Cultural Services Venuesmentioning
confidence: 99%
“…Technology has now been widely used for improving cultural services and is not just limited to academia or libraries (Dalili Saleh et al , 2021; Greene and Groenendyk, 2021; Noh, 2021; Suen et al , 2020; Zhou et al , 2021; Li and Liu, 2022; Xin, 2022). In particular, virtual reality (VR) and augmented reality (AR) has drawn much attention.…”
Section: Using Contemporary Technologies In Cultural Services Venuesmentioning
confidence: 99%
“…Marketing of the library’s physical resources and facilities has been taken to another level where remote users get to see the actual spaces and artifacts regardless of location and time barriers. A study by Greene and Groenendyk (2019), which aimed to ascertain the integration of AR in academic libraries, discovered that AR was less adopted in academic libraries and was offered in-library use only. This presents an opportunity for the future to extend the usage of these to remote users as well.…”
Section: Mobile Augmented Reality Applicationsmentioning
confidence: 99%
“…34 surveys were completed, with participants from 30 institutions (four of the institutions each had two participants). In their 2019 review of academic library websites, Greene and Groenendyk (2021) identified 33 ARL‐member libraries hosting XR programs, thus this sample is fairly representative of current academic library XR programs. Participants' indicated their “highest educational degree attained” as follows: 14.29% (n = 5) bachelors, 60.00% (n = 21) masters, 22.86% (n = 8) doctorate, and 2.86% (n = 1) indicated “other.” Participants indicated their professional identity as follows: 37.21% (n = 16) as technologists, 34.88% (n = 15) as librarians, 6.98% (n = 3) as administrators, and 20.93% as “other” (n = 9; 4 of which identified as instructional designers or educators).…”
Section: Research Questions and Findingsmentioning
confidence: 99%